EFFICACY OF CERVICAL CERCLAGE IN SONOGRAPHICALLY SHORTENED CERVIX IN WOMEN AT MODERATE RISK OF PRETERM DELIVERY: Cervical Cerclage in Women at Preterm Delivery - Choudhry, Abeera; Zafar, Mona; Khan, Sumaira; Masood, Saima; Hafeez, Humaira; Choudhry, Humaira (Pakistan Armed Forces Medical Journal, 2010)
Objective: To compare the efficacy and safety of cervical cerclage following objective shortening of cervix by endovaginal ultrasound with elective cerclage in women at high risk of midtrimester miscarriage or preterm delivery.Study design: Quasi experimental.Place and Duration of study: Military Hospital Rawalpind., January 2005 to July 2008.Material and Methods: Cases of elective cerclage were matched for maternal age, previous history of single mid trimester loss or preterm delivery or preterm rupture of membranes before 34 weeks with women who had selective cerclage if cervical length became < 25mm. All patients were followed up till delivery and outcomes in the two groups were assessed in terms of duration of gestation and neonatal survival.Results: 23 cases of elective cerclage were matched to 24 cases of selective cerclage. Transvaginal ultrasound indicated cerclage was performed in 50% of the control group due to decrease in cervical length. There was no significant difference in the number delivering before 25 weeks 2(8.6 %) versus 3(12.4%), those delivering at gestation>35 weeks 17 (73%) versus 16(66.6%)(p=0.94) . Neonatal survival was also similar 18(78%) versus 19(79%) p=0.96.Conclusion: Cervical length as measured by TVS is the best available technique for predicting preterm labour. In women deemed moderately high risk on the basis of history, sonographic cervical length indicated cerclage appears to reduce cerclage rates without comprising pregnancy outcome